PEMULIHAN SOSIAL DAN EKONOMI MASYARAKAT TERDAMPAK TSUNAMI DI KABUPATEN PANDEGLANG UNTUK MENDUKUNG PEMBANGUNAN DAERAH BERKELANJUTAN - Dedy Hartono; Syamsul Maarif; Deffi Ayu Puspito Sari; W Wilopo (Republic of Indonesia Defense University, 2022)
Post-disaster recovery had to be measured to determine the level of success of the recovery process whether it has returned to pre-disaster condition or conditions that are better than before the disaster or even worse than before the disaster. This study aimed to analyze the social and economic recovery of disaster-affected communities in order to support sustainable regional programs. This study used qualitative research method with a case study research design. The results of the study showed that social recovery in 3 years after the Tsunami, namely in 2021, is 100.08% with the indicator of recovered. Meanwhile, the economic recovery up to 3 years after the Tsunami, namely in 2021, at 99.59% has not yet reached the recovery indicator. The recovered category is based on the calculation results with numbers above 100%. The conclusion of this research was that the effective social and economic recovery will support sustainable regional development because community resilience will be formed. The process of social and economic recovery, the current social condition of the community has recovered on average and the economic condition of the community is nearing recovery, with minimal central government programs. This was due to the resilience of local governments and communities. A strong social and economic community will support the creation of the principle of